THE CORRELATION BETWEEN SLEEP DISORDERS AND ULCERATIVE COLITIS AND OTHER AUTOIMMUNE DISEASES: A SCIENTIFIC REVIEW - Agnieszka Brzezińska; Wojciech Gąska; Ignacy Rożek; Izabela Lekan; Joanna Mazurek; Weronika Tuszyńska; Alicja Sodolska; Michał Lenart; Barbara Madoń; Barbara Teresińska (International Journal of Innovative Technologies in Social Science, 2025)
Ulcerative colitis (UC), a chronic inflammatory bowel disease (IBD), is an autoimmune disease and is increasingly recognised for its bidirectional relationship with sleep disorders. Emerging evidence suggests that sleep disturbances not only exacerbate UC symptoms but may also influence disease activity and relapse rates. Sleep deprivation is increasingly recognized as a significant factor influencing the pathogenesis and progression of autoimmune diseases. This review also synthesizes current evidence on the bidirectional relationship between sleep disturbances and autoimmune conditions, focusing on underlying mechanisms, clinical implications, and potential therapeutic strategies.